Blasco i Canet Josep, teacher and sculptor - Muruzábal del Solar, José María (Huarte de San Juan. Geografía e Historia, 2017)
This article traces the biographical profile, plus analysis of the sculpture, the artist Josep Blasco i Canet. This sculptor born in Valencia in 1943, studied at the Academy of Fine Arts in Valencia and in 1967 arrived in Navarra to devote himself to teaching. In Navarra ended reconciles educational work with sculptural practice. In 1978 he joined the school of Teaching of Pamplona, of which he became director. He undertook to incorporate the school to the Public University of Navarra, where he worked until his retirement in 2013. In addition, since the sixties, he has not stopped working sculpture, performing an extensive production that has managed to move between figuration and abstraction.